Pengaruh Media Pembelajaran Video Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII di SMP Negeri 1 Harian Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Okta Velin Sihotang; Andar Gunawan Pasaribu; Helena Turnip; Raikhapoor Raikhapoor; Eduward Hottua Hutabarat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The research aims to determine the positive influence of video learning media on the learning motivation of Christian Religious Education and Character Education for class VIII students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 Academic Year. The research hypothesis is that there is a positive influence between video learning media on the learning motivation of Christian Religious Education and Characteristics of class VIII students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 Academic Year. Descriptive quantitative research method. The population of all class VIII students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 academic year who are Protestant Christians is 40 people and are also research respondents, therefore this research is a population research. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.567>rtable=0.312 shows that there is a positive relationship between video learning media and student motivation to learn Christian Religious Education and Character. b) Regression equation. c) The determination test shows that the magnitude of the effect is 32.15%. d) Hypothesis testing obtained Fcount=17.907>Ftable=3.23 then H0 is rejected and Ha is accepted. The research concluded that there was a positive influence of video learning media on the learning motivation for Christian Religious Education and Character Education of class VIII students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 Academic Year.